Meningkatkan Kepercayaan Diri Generasi Muda Melalui Pelatihan Public Speaking Pada Siswa Di UPTD SMPN 15 Sinjai - nur akifa rifaii; Nurwahida; R. Firdaus Wahyudi (INKAMKU : Integrasi Akademisi dan Masyarakat yang Berkualitas, 2024)
To contribute and lead the future, the young generation is an agent of change and a determinant of the future survival of the nation. They should be able to communicate well, including speaking in public. Speaking in public is not the same as speaking at home. Although not everyone has the ability to speak in public, everyone has a ability to talk. Just like today's younger generation, which needs guidance and attention to be able to perform with confidence in public. Early adolescence is an important period in a person's development, including the ability to speak in public. This ability will be very useful to them. Many high school students, especially the ninth grade, still feel distressed and nervous when speaking in public. This can cause them difficulties in conveying their ideas and ideas clearly. As a result, public speaking training should be designed specifically for ninth-grade high school students, especially in Sinjai 15th grade high school. The aim is to provide early supplies to students who will enter high school, as they will speak more often in public, such as in discussions in classes, presentations, and other events related to speaking in public.